The Mediating Role of Absorptive Capacity in the Relationship between Digital Transformation Strategy, Customer Experience, and Innovation Toward Business Performance - Dita, Alifa Putri; Dewi, Puspa Sukma; Aini, Indah Nur; Azizah, Fauzia (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
Digital transformation has become a key catalyst in creating value and competitive advantage, especially for Micro, Small, and Medium Enterprises (MSMEs) in the digital economy era. This study aims to examine the mediating role of absorptive capacity in the relationship between digital transformation strategy, innovation, customer experience, and business performance. Using a quantitative approach and a causal explanatory design, the study involved 700 respondents from food and beverage MSMEs in West Java. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS. The results show that digital transformation strategy and innovation have a significant positive effect on absorptive capacity, which in turn has a direct impact on both customer experience and business performance. Moreover, absorptive capacity significantly mediates the influence of strategic variables on business performance, highlighting the importance of internal capabilities in managing external knowledge. This study contributes to the literature by offering a theoretical framework that integrates the Resource-Based View (RBV), Dynamic Capabilities, and Knowledge-Based View (KBV) in the MSME context. The managerial implications suggest that adopting digital technology should be accompanied by strengthening organizational learning systems to sustainably improve business performance.